2008
DOI: 10.1097/pas.0b013e31817dc37c
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Expression of Collapsin Response Mediator Protein 5 (CRMP5) is a Specific Marker of High-grade Lung Neuroendocrine Carcinoma

Abstract: The diagnosis of high-grade neuroendocrine tumors has strong clinical relevance because it identifies patients at higher risk of an unfavorable outcome who should receive multimodal treatment. However, these tumors can be mistaken for poorly differentiated nonsmall cell carcinoma or carcinoid lung tumors. In fact, no immunohistochemical marker can currently distinguish between histologic lung subtypes. Because the collapsin response mediator protein (CRMP) family is involved in an autoimmune disease associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…This original finding is in favor of a role of CRMP5 in the transition phase between proliferative and non-proliferative stages, suggesting that CRMP5 might play an active role in adult neurogenesis by taking part to the repression of proliferation and/or to the induction of the first stages of neuronal differentiation. The high expression level of CRMP5 in aggressive neuroendocrine tumors [23] highlights the likely involvement of this protein in the balance between proliferation and differentiation in different cell types and in both physiological and pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This original finding is in favor of a role of CRMP5 in the transition phase between proliferative and non-proliferative stages, suggesting that CRMP5 might play an active role in adult neurogenesis by taking part to the repression of proliferation and/or to the induction of the first stages of neuronal differentiation. The high expression level of CRMP5 in aggressive neuroendocrine tumors [23] highlights the likely involvement of this protein in the balance between proliferation and differentiation in different cell types and in both physiological and pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Human GBM biopsies fixed in AFA were stained using Ventana Ultraview peroxydase system combined with the following primary antibodies: anti-CRMP5 polyclonal rabbit antibody (1:100; refs. 10,14); anti-Hes1 (1:30; Cell Signaling Technology, 11988); and anti-Notch1 (1:50; Abcam ab52627).…”
Section: Immunostainingmentioning
confidence: 99%
“…1B). Subcellular fractionation of GBM extracts and immunolocalization using a CRMP5 polyclonal antibody demonstrated cytoplasmic and nuclear forms of CRMP5 in GBM tumors, cell lines and only in GBM_SC1 xenograft ( CRMP5 expression in GBM predicts lower patient survival and is related to tumor proliferation CRMP5 protein immunohistochemical expression in GBM tumors was obtained from 183 GBM biopsies using a CRMP5 polyclonal antibody previously validated with lung tumor biopsies (14). Two CRMP5 expression patterns emerged: low CRMP5 expression (CRMP5 LOW : N ¼ 23, 12.6%) was characterized by weak, heterogeneously dispersed CRMP5 staining in 0% to 10% of cells, and high CRMP5 expression (CRMP5 HIGH : N ¼ 160, 87%) was characterized by highly diffuse cytoplasmic staining of CRMP5 in approximately 90% of tumor cells ( Fig.…”
Section: Crmp5 Protein Is Expressed In Human Gbm and Established Gbm-mentioning
confidence: 99%
See 1 more Smart Citation
“…Both GSK-3β and WAVE-1 were involved in CRMP mediated axon outgrowth, indicating CRMP has diverse functions in different cellular processes. Other CRMP family members involved in cancer include CRMP2, CRMP4 and CRMP5, all were reported associated with different cancer cell migration, invasion, differentiation and clinical outcome in certain tumor types (16)(17)(18)(19). In our previous study (20), we first identified CRMP4 as a prostate cancer metastasis suppressor factor by proteomics approach and verified that CRMP4 suppress prostate cancer cell line proliferation and invasion in vitro and the downregulation of CRMP4 in metastatic tumor may be due to the methylation of the CpG island within the promoter region of the CRMP4 gene.…”
Section: Introductionmentioning
confidence: 99%